Quantitative Optical Coherence Tomography Angiography in Patients with Moyamoya Vasculopathy: A Pilot Study. (2nd November 2021) - Khan, Haaris M.; Lo, Julian; Sarunic, Marinko V.; Gooderham, Peter A.; Yip, Samuel; Sheldon, Claire A.; Wirth, Magdalena A.
ABSTRACT: Moyamoya (MM) disease is a chronic cerebrovascular disease that can lead to progressive stenosis of the terminal portions of the internal carotid arteries and their proximal branches. We sought to investigate and quantify retinal vascular changes in patients with MM vasculopathy (MMV) using optical coherence tomography angiography (OCTA) compared to healthy controls. Our findings reveal retinal microvascular changes in patients with MMV and highlights the potential of OCTA imaging for the detection of subclinical retinal pathology.